Case report: Depressive disorder with peripartum onset camouflages suspected intracranial tuberculoma - Zakia, Halwa; Iskandar, Shelly (Frontiers in Psychiatry, 2022)
Background: Co-occuring psychological symptoms and rare medical illnesses like intracranial tuberculoma add difficulties in diagnosing and treatment. The present report discussed a rare case of a young woman with tuberculoma and depressive disorder with peripartum onset. Case presentation: The patient was a 22-year-old woman. She underwent a caesarean section due to premature rupture of the membrane. She had developed behavioral changes for three months before admission and had been brought to general practitioner for several times during pregnancy. Her symptoms worsen after she underwent a caesarean section. She refused to answer doctor’s and family’s questions and she showed symptoms of depression. She was diagnosed with depressive disorder with peripartum onset and treated according to her diagnosis. However, she also experienced intermittent headaches which lead to suspicion that there was an organic causes for her complaints. Computed tomography (CT) was done and revealed suspected intracranial tuberculoma and meningitis. She died due to respiratory distress before she got adequate treatment for her illnesses. Conclusion: The possibility of neurocognitive disorder due to infection such as intracranial tuberculoma should be considered as an additional diagnosis (co-occuring disease) or differential diagnosis in people who develop psychiatric symptoms, especially in areas with high tuberculosis incidence.